PENINGKATAN HASIL BELAJAR IPAS PADA SISWA KELAS V SDN 14 SIGUNTUR KABUPATEN PESISIR SELATAN - Amelia Fitri, Nafla; Ahmad, Syafri; Amini, Risda; Media, Afriza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes in Integrated Science and Social Studies (IPAS) among Grade V students at SDN 14 Siguntur, Pesisir Selatan Regency. The low achievement was influenced by students’ lack of focus, low learning motivation, and limited curiosity, which resulted in boredom and reluctance to participate in group activities. From the teacher’s perspective, learning was still dominated by lecture-based methods using standard teaching modules without innovation, and learning resources were limited to textbooks and student worksheets. Therefore, this study aimed to describe the improvement of IPAS learning outcomes through the implementation of the Discovery Learning model for Grade V students. This research employed Classroom Action Research (CAR) using qualitative and quantitative approaches. The study was conducted in two cycles, with Cycle I consisting of two meetings and Cycle II consisting of one meeting. Each cycle included the stages of planning, implementation, observation, and reflection. The research subjects were one teacher and 23 Grade V students. Research data were obtained from teaching module assessments, learning process observations, and student learning outcomes. The results showed that the teaching module assessment in Cycle I achieved an average score of 85.4% (B), which increased to 91.6% (SB) in Cycle II. Teacher and student learning activities improved from 89.06% (B) in Cycle I to 96.87% (SB) in Cycle II. Student learning outcomes increased from an average score of 74.44% (C) to 85.86% (B). It can be concluded that the Discovery Learning model effectively improves IPAS learning outcomes.